2000
DOI: 10.1080/10550490050172254
|View full text |Cite
|
Sign up to set email alerts
|

Addiction, Community and State: A Review

Abstract: As clinicians, we are well aware of the importance of drug supply, price, availability, and access in propagating and maintaining illicit drug use, abuse, and addiction. However, we tend to be silent on these topics, leaving them to elected and appointed government leaders. The author proposes that our remaining silent is analogous to an infectious disease expert remaining silent on water supply and sewage in the midst of a cholera epidemic. It is not only unseemly for us to remain silent, it is unprofessional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Some state and federal prisons permit MAT for opioid-dependent prisoners, but the US criminal justice system has generally been reluctant to accept MAT (Magura et al, 2009; McMillan and Lapham, 2005; Nunn et al, 2009; Rich et al, 2005; Westermeyer, 2000). In 1999, a 202-court survey found that 39% of drug courts made methadone available to participants (Peyton and Gossweiler, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Some state and federal prisons permit MAT for opioid-dependent prisoners, but the US criminal justice system has generally been reluctant to accept MAT (Magura et al, 2009; McMillan and Lapham, 2005; Nunn et al, 2009; Rich et al, 2005; Westermeyer, 2000). In 1999, a 202-court survey found that 39% of drug courts made methadone available to participants (Peyton and Gossweiler, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A major obstacle to expanded access to methadone maintenance for inmates in the U.S. is the unfortunate and undeserved stigma that has come to be associated with it, i.e., a common belief among the public (Blansfield, 1996), treatment providers (Kang et al, 1997), and public authorities, including the criminal justice system (Simpson and Knight, 1998; Westermeyer, 2000; McMillan and Lapham, 2005), that methadone “substitutes one addiction for another” and is not a true tool of recovery. For example, staff of a large Southwestern jail “described a tremendous amount of animosity towards drug addicts and lumped methadone maintenance treatment recipients together with heroin addicts and criminals.” They were also concerned about methadone’s euphoria-inducing potential: “methadone is just another crutch, a way to stay numb” (McMillan and Lapham, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Drug abuse predominantly represents a major problem worldwide that is included in clinical as well as legal aspects [1,2]. According to the World Drug Report in 2018, about 275 million people worldwide (roughly 5.6% of the global population aged 15-64 years) used illicit drugs at least once in 2016 [3].…”
Section: Introductionmentioning
confidence: 99%